Comparison of intention to immigration and relative factors among undergraduate nursing students at universities of medical sciences in Kerman, Iran and Erbil, Iraq in 2023 - Sara Mehrabi; Jamileh Farokhzadian; Hemen Kareem Qadir; Azam Bazrafshan; Tania Dehesh; Zohreh Khoshnood (BMC Nursing)
Abstract Background & aim Migration is a phenomenon that both developed and developing countries are struggling with. Given that the decision to migrate is formed during the student period, the present study aimed to compare the degree of intention to migrate and related factors in undergraduate nursing students at universities of medical sciences in Kerman, Iran and Erbil, Iraq in 2023. Methods This cross-sectional descriptive study focused on a sample of nursing students from Kerman University of Medical Sciences, Polytechnic, and Hawler University of Iraq. To ensure a representative sample, a simple random sampling method was utilized. The sample size conducted on 487 nursing students. 272 students selected from Kerman University of Medical Sciences and 215 students from Erbil University in Iraq. Data collection was performed using a structured questionnaire, which included items related to the intention to migrate, factors influencing this intention, and demographic information. The collected data were analyzed using both descriptive and correletional statistical methods, And SPSS-22 software was used. Findings The data revealed that 69.5% of Iranian nursing students and 58.1% of Iraqi nursing students intended to emigrate. The most important reasons for the intention to migrate among Iranian students were better quality of life (4.39), the balance between income and living expenses (4.35), and economic and social stability (4.34). In addition, Iraqi students reported better quality of life (3.89), professors’ behavior with students (3.70), and professors’ teaching methods (3.56) as the reasons behind their intention to migrate. Conclusion Iranian and Iraqi nursing students had a significant intention to migrate. Thus, effective policies should be adopted to reduce the intention to migrate among nursing students. Moreover, interventional studies need to explore the factors that can motivate this group of students to stay in the country. Clinical trial number Not applicable.